Mechanistic and pharmacologic insights on immune checkpoint inhibitors. (June 2017) - Sweis, Randy F.; Luke, Jason J.
Graphical abstract: Abstract: The concept of augmenting the immune system to eradicate cancer dates back at least a century. A major resurgence in cancer immunotherapy has occurred over the past decade since the identification and targeting of negative regulators with antibody therapies to augment the anti-tumor immune response. Unprecedented responses across a broad array of cancer types elevated this class of therapies to the forefront of cancer treatment. The most successful drugs to date target the cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) and programmed cell death-1 (PD-1) pathways. The immune biology of these pathways was illuminated through thoughtful pre-clinical experiments over the past 20 years. The characterization of these negative immune regulators, also known as immune checkpoints, subsequently led to the successful clinical development four drugs in six different cancer types to date, and progress continues. Despite these successes, significant challenges remain including the development of predictive biomarkers, recognition and management of immune related toxicities, and elucidating and reversing mechanisms of primary and secondary resistance. Ongoing work is expected to build upon recent accomplishments and allow more patients to benefit from this class of therapies.